An investigation of water quality considerations for premise plumbing systems in buildings - Kalan, Duygu, author; Ozbek, Mehmet, advisor; Omur-Ozbek, Pinar, advisor; Grigg, Neil, committee member; Dooley, Gregory, committee member (Colorado State University. Libraries, 2021)
Providing potable and palatable waterq to their consumers is a top priority for drinking water treatment utilities in the US. To ensure the safety of the drinking water, disinfection methods have been applied for over a century. Chlorine is the most extensively used disinfectant to control waterborne pathogen activities. Despite its effectiveness, chlorine is known to react with natural organic matter (NOM) and produce disinfection by-products (DBPs) (e.g., trihalomethanes and haloacetic acids) that are known to be harmful to humans. Currently, DBPs are regulated at the distribution system level. However, premise plumbing systems are unique and different from water distribution systems. Moreover, there are knowledge gaps for premise plumbing in residential and non-residential buildings under routine operations, and that has not been fully understood for different operation scenarios (e.g., use of water-efficient fixtures in conventional buildings) and building types (e.g., green-certified buildings). The primary purpose of this dissertation was to contribute to the body of knowledge on water quality in premise plumbing systems by addressing some of the knowledge gaps identified in the literature. This dissertation comprises three independent but complementary studies. Each study focused on essential aspects of water quality in premise plumbing systems as follows: i) identifying the effects of building type (e.g., conventional vs. green-certified) on water quality in premise plumbing systems, ii) providing a comprehensive literature review on existing contaminant prediction models for premise plumbing systems, and iii) developing a DBP prediction tool for premise plumbing systems. In the first study, effects of building type on premise plumbing water quality were addressed. For this purpose, trihalomethanes (THMs) and water quality parameters, including temperature, pH, free chlorine levels, and total organic carbon (TOC) were collected and compared between a combined conventional and green-certified (i.e., water-efficient) building drinking fountains. Even though the distributed water quality to the green and conventional building sides was the same, statistically significant differences in water quality parameters and TTHMs were observed due to the changes in water chemistry in the premise plumbing systems. The study findings point out the importance of the plumbing pipe age and its impacts on water chemistry. In the second study, a state-of-the-art review was conducted to provide background information on water quality and indoor air quality models that have been implemented in residential and non-residential building premise plumbing systems and indoor air environments. A systematic literature search was conducted in the Compendex, Web of Science, IEEE Explore, Science Direct, and PubMed databases. A total of 22 contaminant prediction modeling studies for premise plumbing and 12 for indoor air quality were reviewed in this study. Among the premise plumbing models, lead and copper prediction models have drawn more attention from researchers than any other contaminants. Due to increased inhalation exposure levels, shower models have been excessively included in risk exposure studies. This review aimed to draw attention to the research needs in modeling approaches, identify the gaps in the literature, and provide a baseline for future research attempts. In the third study, a chloroform prediction model was developed and incorporated into a simulation software to predict chloroform concentrations in a premise plumbing system for eight hours of water stagnation. The model coefficients were determined with the bench-scale experiments based on water quality parameter ranges that can be seen in premise plumbing systems. Chloroform concentrations were tested in a two-story townhouse; experimental and model prediction results were compared. The chloroform prediction model underpredicted chloroform concentrations by 27-37% compared with the house measurements. This study represents an important initial attempt in developing a simulation-based water quality prediction model, which can be implemented in premise plumbing systems. This study contributes to the body of knowledge on water quality in premise plumbing systems by providing a better insight into the effects of conventional and green-certified buildings, shedding light on the current state of numerical modeling research, and implementing a chloroform prediction tool in premise plumbing systems.
Keywords: disinfection by-products; premise plumbing; water quality; green building; conventional building; trihalomethanes